The influence of CEO narcissism on the design of compensation mechanisms: is there a bright side on this personality trait? - Azevedo, Yuri Gomes Paiva (2022)
Grounded on the view that Chief Executive Officer (CEO) individual characteristics, such as CEO narcissism, could shed light on why firm performance is weakly or not significantly associated with CEO compensation, this doctoral dissertation aims to examine whether CEO narcissism has a moderating effect on the pay-performance sensitivity. To carry out our investigation, we use a sample of 1,057 non-financial U.S. firms (8,869 firm-year observations), during the period 2002-2018, employing System Generalized Method of Moments (SYS-GMM) regressions due to the endogenous relationship between CEO compensation and firm performance. Our main results indicate that CEO narcissism moderates negatively the association between CEO compensation and firms performance. Therefore, instead of can be viewed as a \"bright side\" by aligning CEOs\' and shareholders\' interests, CEO narcissism can be viewed as a \"dark side\" as reduces the pay-performance sensitivity, not reflecting the recommended corporate governance practices. This finding is robust to alternative measures of pay-performance sensitivity, and further robustness checks indicate that our results are not driven by CEO overconfidence. In order to find a possible \"bright side\" of CEO narcissism in the design of executive compensation, we conduct a supplemental analysis that examines the relationship between CEO narcissism and a specific managerial compensation mechanism that takes effect upon a change in control of the firm, namely golden parachute. This supplemental analysis also indicates that narcissism act as a \"dark side\", considering that more narcissistic CEOs will tend to reduce the likelihood of adopting this anti-takeover device, thereby, maintaining firm\'s less protected against takeovers threats. Therefore, this doctoral dissertation suggests that CEO narcissism can be viewed as a \"dark side\" in the design of executive compensation. Thus, we contribute to the literature since, to the best of our knowledge, we provide the first empirical evidence of the moderating effect of CEO narcissism both on the pay-performance sensitivity and on the adoption of golden parachutes. We also shed light on two \"dark side\" effects of CEO narcissism that might contribute to shareholders and potential investors by showing that CEO narcissism reduces the propensity of aligning the interests of managers for higher levels of compensation with investors\' interests for better firm performance, and in the likelihood of adopting golden parachutes to protect against takeovers threats. These novel findings could also be useful for board members, as they could consider this psychological aspect when proposing compensation schemes to CEOs.